Helicobacter pylori seropositivity and its associated factors in children from suburban area in Yangon - Win, Phyu Phyu; Win, Lei Lei; Naing, Zay Yar (International Journal Of Community Medicine And Public Health, 2024)
Background: H. pylori has infected about 50% of the global population. The infection rate in children differs across countries, being lower in high-income nations (34.7%) compared to low- and middle-income countries (50.8%). This study aimed to assess the risk factors associated with the seroprevalence of H. pylori infection among individuals aged 2 to 16 in Insein Township, Yangon Division, Myanmar. Methods: A community-based cross-sectional study was conducted in Insein Township. A total of 193 children, aged 2 to 16 years and of both genders, were randomly selected. An in-house enzyme-linked immunosorbent assay (ELISA) was used to determine serum H. pylori IgG antibodies. Statistical analysis was performed using chi-squared tests, and mean scores between groups were compared using two-sample t-tests. Results: Out of 193 children, 130 (67.36%) were tested positive for H. pylori antibodies. The average age of the participants was 7.6±3.85 years. Although H. pylori positivity was highest (71.01%) among those with birth order 1 and lowest (56.52%) in those with birth order 4 and above, it was not statistically significant. There was a higher percentage of H. pylori seropositivity among children with recurrent abdominal pain (87.77%). The rate of H. pylori antibody positivity was higher among those with a family history of peptic ulcer (85.71%). Conclusions: The infection rate of H. pylori remains high among children in developing countries, highlighting the need for comprehensive prevention and treatment programs. Early diagnosis can greatly reduce complications later in adulthood and could have a significant impact on the country’s socio-economic status.